Effect of mixing soil saprophytic fungi with organic residues on the response of Solanum lycopersicum to arbuscular mycorrhizal fungi. (4th January 2015) - Almonacid, L.; Fuentes, A.; Ortiz, J.; Salas, C.; Garcia‐Romera, I.; Ocampo, J.; Arriagada, C.
Abstract The effect of the dual inoculation with arbuscular mycorrhizal (AM) and saprophytic fungi and a combination of wheat straw and sewage sludge residues were studied by determining their effect on dry weight of tomato and on chemical and biochemical properties of soil. Incubation of organic residue (sewage sludge combined with wheat straw) with saprophytic fungi and plant inoculation with mycorrhizal fungi was essential to study plant growth promotion. Soil application of organic residues increased the dry weight of tomato inoculated with Rhizophagus irregularis. The greatest shoot dry mass was obtained when the organic residues were incubated with Trichoderma harzianum and applied to AM plants. However, the greatest percentage of root length colonized with AM in the presence of the organic residues was obtained with inoculation with Coriolopsis rigida. The relative chlorophyll was greatest in mycorrhizal plants regardless of the presence of either saprophytic fungus. The presence of the saprophytic fungi increased soil pH as the incubation time increased. Soil nitrogen and phosphorus contents and acid phosphatase were stimulated by the addition of organic residues, and contents of N and P. Total N and P content in soil increased when the organic residue was incubated with saprobe fungi, but this effect decreased as the incubation period of the residue with saprobe fungi increased. The same trend was observed for soil β‐glucosidase and fluorescein diacetate activities. The application of organic residues in the presence of AM and saprophytic fungi seems to be an interesting option as a biofertilizer to improve plant growth and biochemical parameters of soils.